2020
DOI: 10.1364/oe.388943
|View full text |Cite
|
Sign up to set email alerts
|

Towards polarization-based excitation tailoring for extended Raman spectroscopy

Abstract: Undoubtedly, Raman spectroscopy is one of the most elaborated spectroscopy tools in materials science, chemistry, medicine and optics. However, when it comes to the analysis of nanostructured specimens, accessing the Raman spectra resulting from an exciting electric field component oriented perpendicularly to the substrate plane is a difficult task and conventionally can only be achieved by mechanically tilting the sample, or by sophisticated sample preparation. Here, we propose a novel experimental method bas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Consequently, experiments rely on elastic dark-field scattering spectra obtained under quasi-plane wave excitation to infer the nanocavity spectrum and which mode is excited at a particular laser wavelength [20,25]. Not only is this approach underestimating or neglecting the contribution of 'dark' modes (which do not couple well to incident plane waves but can be efficiently excited by scatterers or emitters in the near field), it is also unable to make prediction as to the relative input coupling rate of a strongly focused laser beam to a particular mode, which can depend not only on laser wavelength, but also on the near field polarization at the focus [26][27][28][29][30]. Knowledge of the cavity input coupling rate is required to infer the intracavity excitation number, which in turns govern all optically-driven processes in various applications including SERS, photochemistry and photocatalysis, plasmon-enhanced luminescence, nonlinear optics and frequency conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, experiments rely on elastic dark-field scattering spectra obtained under quasi-plane wave excitation to infer the nanocavity spectrum and which mode is excited at a particular laser wavelength [20,25]. Not only is this approach underestimating or neglecting the contribution of 'dark' modes (which do not couple well to incident plane waves but can be efficiently excited by scatterers or emitters in the near field), it is also unable to make prediction as to the relative input coupling rate of a strongly focused laser beam to a particular mode, which can depend not only on laser wavelength, but also on the near field polarization at the focus [26][27][28][29][30]. Knowledge of the cavity input coupling rate is required to infer the intracavity excitation number, which in turns govern all optically-driven processes in various applications including SERS, photochemistry and photocatalysis, plasmon-enhanced luminescence, nonlinear optics and frequency conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Because near-field intensities for all gap modes are tightly confined within the spacer material, direct and quantitative analysis via near-field scanning probe or electron energy loss spectroscopy has not been achieved. Consequently, experiments rely on elastic dark-field scattering spectra obtained under quasi-plane wave excitation to infer the nanocavity spectrum and which mode is excited at a particular laser wavelength. , Not only is this approach underestimating or neglecting the contribution of “dark” modes (which do not couple well to incident plane waves but can be efficiently excited by scatterers or emitters in the near field), it is also unable to make prediction as to the relative input coupling rate of a strongly focused laser beam to a particular mode, which can depend not only on laser wavelength but also on the near field polarization at the focus. Knowledge of the cavity input coupling rate is required to infer the intracavity excitation number, which in turns govern all optically driven processes in various applications including surface-enhanced Raman spectroscopy (SERS), photochemistry and photocatalysis, plasmon-enhanced luminescence, nonlinear optics, and frequency conversion. Its role and physical meaning has been evidenced using various formalisms: indirectly via quantum master equations, , in plasmon induced transparency, and also in the context of molecular cavity optomechanics, which aims at a more complete description of vibrational and plasmonic correlations and dynamics in SERS.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the last two decades have shown that by taking advantage of the subwavelength features in structured and confined fields, the range of applications can be drastically extended and existing applications can be optimized. The rich and intriguing features of all kinds of nanoscale fields, for example, related to longitudinal fields or optical angular momenta, ,, have paved the way for bespoke techniques in the context of precise nanometrology, nanoscale traffic control for integrated photonics, advanced nanospectroscopy, , excitation of dark modes or anapoles, , and optical trapping. Furthermore, the developments in the field of extraordinary angular momenta of light, an inherent feature of confined fields, also set the stage for further developments in quantum optics …”
Section: Introduction To the Shape Of Light: Paraxial And Nonparaxial...mentioning
confidence: 99%